Comparative analysis of twenty-five compounds in different parts of Astragalus membranaceus var. mongholicus and Astragalus membranaceus by UPLC-MS/MS - Li, Yuan (J Pharm Anal, 2019)
As a traditional Chinese medicine, the root of Astragalus membranaceus var. mongholicus (AMM) or A. membranaceus (AM) has been widely used in China and other Asian countries for thousands of years. Till now, the flavonoids, phenolic acids and saponins are considered as the main active components contributing to their therapeutic effect in these plants. In order to clarify the distribution and contents of these compounds in different organs of these plants, a rapid and sensitive analytical method for simultaneous determination of 25 active compounds including seven types (i.e. dihydroflavones, isoflavane, isoflavones, flavones, pterocarpans, phenolic acid and saponins) within 10 min was established using ultra-pressure liquid chromatography coupled with tandem mass spectrometry (UPLC–MS/MS). Then, the established method was fully validated and successfully applied to the determination of the contents of these analytes in different parts (root, rhizome, stem, leaf and flower) of AMM and AM. The results indicated that the contents of the same type of compounds in two different species plants were significantly different. Moreover, the obvious differences were also found for the distribution and contents of different type of compounds in five organs of the same species. The present study could provide necessary information for the rational development and utilization of AMM and AM resource.